Doing qualitative research : the craft of naturalistic inquiry - Beuving, Joost; Vries, G. C. de (Geert C.) (Amsterdam University Press, 2015)
Naturalistic inquiry is about studying people in everyday circumstances using ordinary means. It strives to blend in-respecting people in their daily lives, taking their actions and experiences seriously while not interfering-in order to come to theoretical understanding. This textbook offers guidance, combining thoughtful reflection with practical tips. It is written for undergraduate and graduate students in social science; for practitioners in social work, healthcare, policy advice, and organizational consultancy; and for all who have a genuine interest in society and its members.